Effectiveness of a working memory intervention program in children with language disorders. Issue 1 (2nd January 2019) - Acosta, Victor; Hernandez, Sergio; Ramirez, Gustavo
ABSTRACT: The aim of this study was twofold: first, to obtain a neuropsychological characterization of children with language disorders, and second, to evaluate the effectiveness of an intervention program on working memory. We used a pretest-instruction–posttest design, carefully identifying a sample of 32 children with language disorders whom we then evaluated for short-term verbal and visuospatial memory, verbal and visuospatial working memory, attention, processing speed, and lexical-semantic skills. We then implemented an intervention program on working memory consisting of 72 sessions of 15 minutes each, after which we repeated the neuropsychological assessment of these functions. Children with language disorders performed worse than children in the control group in all memory tasks evaluated and in the lexical-semantic processing task. After the intervention, children with language disorders showed a significant increase over their own previous performance in all variables. Children with language disorders show significant cognitive deficits and not just linguistic impairment. We offer conclusive findings on the effectiveness of the intervention program used. Finally, we obtained partial support for the existence of a causal link between improved performance on memory tasks and performance in a lexical-semantic task.